How do collaborations in luxury brands contribute to building a unique and recognizable brand identity? - Vianello, Elena (2024)
This research explores the role of strategic collaborations in shaping purchase intention and brand perception within the fashion industry, focusing on Moncler as a case study. The study examines how collaborations, involving both designers and celebrities, influence brand identity and consumer behavior, drawing on a comprehensive literature review, case studies and a detailed empirical analysis. Initially, the research delves into the evolution of brand perception theories, highlighting the shift from functional attributes to emotional and experiential connections. It also discusses how collaborations contribute to brand equity by enhancing perceived value and fostering consumer loyalty. The historical analysis traces the impact of pioneering collaborations, such as Gucci with North Face and Louis Vuitton with Supreme, illustrating how these partnerships drive innovation, expand markets, and adapt to digital and cultural shifts, while also addressing potential risks like brand dilution.The case study of Moncler highlights its strategic use of collaborations to build a unique and recognizable brand identity, focusing on partnerships with figures like Pierpaolo Piccioli and Alicia Keys. These collaborations demonstrate the blending of high fashion with functionality and underscore the brand’s creative and marketing strategies, consumer reception, and financial impact.A comparative analysis of four collaboration scenarios involving mainstream and luxury brands paired with designers or celebrities reveals that collaborations generally enhance purchase intention across both brand types. Designer collaborations tend to enhance perceived exclusivity in luxury contexts, while celebrity partnerships boost engagement and purchase intention for mainstream brands. Mediation analyses identify perceived exclusivity and engagement as critical factors in shaping consumer responses, emphasizing the need for brands to align collaboration types with their positioning to maximize impact.Overall, the findings demonstrate that strategic collaborations are a powerful tool for fashion brands seeking to innovate and connect with diverse consumer groups. By aligning with designers, artists, and cultural icons, brands can enhance their equity, broaden their reach, and strengthen their market position in the competitive fashion industry.